Hubungan perilaku self management dengan kadar gula darah pada penderita diabetes melitus tipe II - Fadhila, Vivi Nur; Kartinah, Kartinah (Holistik Jurnal Kesehatan, 2025)
Background: In 2021, an estimated 536.6 million people worldwide, or 9.3% of the population, had type II diabetes mellitus (DM). In Indonesia, the prevalence of type II DM increased from 6.9% in 2013 to 8.5% in 2018. In Central Java, the prevalence was 1.59%. At the Gatak Sukoharjo Community Health Center, in June 2005, 129 new sufferers were recorded, or 46.4% of the population of 46,754 people. One of the key actions is self-management, including blood sugar monitoring for individuals with diabetes. Purpose: To determine the relationship between self-management behavior and blood sugar levels in individuals with type II diabetes mellitus (DM). Method: Descriptive correlational research with cross sectional design to analyze the relationship between self-management behavior and blood sugar levels in type II DM patients. Sampling using total sampling technique and obtained 75 respondents who met the inclusion criteria. Result: The majority of individuals with type II diabetes mellitus had low self-management (36.0%) and high blood sugar levels (74.7%), indicating poorly controlled conditions. Most respondents were female (72.0%), had an education level of elementary school or equivalent (53.3%), were unemployed (44.0%), had been living with the disease for more than 10 years (85.3%), and were aged 56-65 years (49.3%). The Spearman Rank test analysis showed a significant relationship between self-management and blood sugar levels (p = 0.001). Conclusion: There is a significant relationship between self-management behavior and blood sugar levels in individuals with type II diabetes mellitus (DM).   Keywords: Diabetes Mellitus (DM) Type II; Blood Sugar Levels; Self Management Behavior.   Pendahuluan: Pada tahun 2021, diperkirakan 536.6 juta orang di dunia 9.3% populasi mengidap diabetes melitus (DM) tipe II. Di Indonesia, prevalensi DM tipe II meningkat dari 6.9% pada 2013 menjadi 8.5% pada 2018. Di Jawa Tengah, prevalensinya sebesar 1.59%. Di Puskesmas Gatak Sukoharjo, pada Juni 2005 tercatat 129 pengidap baru 46.4% dari total populasi 46,754 jiwa. Salah satu yang harus dilakukan adalah self management, termasuk pemantauan kadar gula darah bagi penderita diabetes. Tujuan: Untuk mengetahui hubungan antara perilaku self management dengan kadar gula darah pada penderita diabetes melitus (DM) tipe II. Metode: Penelitian deskriptif korelasi dengan desain cross sectional untuk menganalisis hubungan perilaku self-management dan kadar gula darah pada pasien DM tipe II. Pengambilan sampel menggunakan teknik total sampling dan didapatkan sebanyak 75 responden yang memenuhi kriteria inklusi. Hasil: Mayoritas pengidap diabetes melitus (DM) tipe II memiliki self management rendah (36.0%) dan kadar gula darah tinggi (74.7%), hal ini mencerminkan kondisi tidak terkontrol. Sebagian besar responden adalah wanita (72.0%), tingkat pendidikan SD/sederajat (53.3%), tidak bekerja (44.0%), mengidap penyakit >10 tahun (85.3%), dan berusia 56-65 tahun (49.3%). Analisis uji Rank Spearman menunjukkan hubungan signifikan antara self management dan kadar gula darah (p = 0.001). Simpulan: Terdapat hubungan perilaku self management dengan kadar gula darah pada penderita diabetes melitus (DM) tipe II.   Kata Kunci: Diabetes Melitus (DM) Tipe II; Kadar Gula Darah; Perilaku Self Management.